(untitled) (Revista Investigación & praxis en CS Sociales, 2024)
This study examines the implementation of cognitive and metacognitive strategies, based on John Flavell’s theory, to improve the reading comprehension of eighth grade students at the Bajo San Francisco Educational Institution, located in Santander de Quilichao, Cauca. Using a qualitative approach and pedagogical action research methodologies, workshops focused on the development of cognitive and metacognitive skills were conducted. The results showed that these strategies significantly increased students’ ability to retain and comprehend information, as well as to identify grammatical rules and perform critical analysis of texts. These findings highlight the effectiveness of cognitive and metacognitive strategies in strengthening reading comprehension in middle school, and confirm the relevance of Flavell’s theory in this context. The research provides a valuable reference for future research and pedagogical practices aimed at improving reading comprehension.